PENYULUHAN PEMANFAATAN RUMPON PERMUKAAN DAN RUMPON DASAR DI DESA SAMINYAMAU KECAMATAN PULAU RAO - kour, femsy; Akerina, Febrina O.; Pattiasina, John Raimond (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Hein Namotemo, 2026)
Saminyamau Village is one of the villages in Rao Island District, Morotai Island Regency, most of which have livelihoods as fishermen. Fishermen conducted an operation of catching around the waters of Saminyamau Village, around the fishing aids area, about 20 minutes from Saminyamau Village. The waters of Saminyamau Village have abundant fisheries resources and fish caught in this event are dominated by grouper, snapper, tuna, skipjack and flying fish. The problem encountered is that the people of Saminyamau Village use surface fishing aids to catch fish and surface fishing aids installed are still close to the coastline and the distance between fishing aids is still close. Fishing aids that are too close to each other can cause fish that are interested in gathering in one particular fishing aids, thereby reducing the effectiveness of other fishing aids. This can reduce the overall catch of fishermen. The purpose of the implementation of this dedication activity is to provide knowledge and understanding of the benefits of the surface and basic fishing aids for the Saminyamau Village fishermen and increase public knowledge about the placement of fishing aids in the Fisheries Management Area. This activity was carried out in the form of counseling at Saminyamau Beach, Rao Island District, Morotai Island Regency which was attended by 60 people.